How Painters Cope with Stress/A Qualitative Research Using Interpretative Phenomenological Analysis - Chronopoulou Myrsini; Louka Penelope (2013)
Introduction, Cause of Stress, Stress Symptoms, Copying with Stress, Stress Management, Methodology, Design, Participants, Materials, Procedure, Analysis, Rerefences.